The kinetics of the alkaline degradation of daptomycin - Muangsiri, Walaisiri; Kirsch, Lee E. (Journal of pharmaceutical sciences, 2001)
The aqueous degradation of daptomycin, a lipopeptide antibiotic, was investigated as a function of substrate concentration (0.5–10.0 mM), pH (9.0–10.5), buffer concentration (0.06–0.20 M borate, glycinate, or carbonate buffers), temperature (20–50°C), and ionic strength (0.1–0.8). The primary degradation pathway was determined by electrospray‐mass spectroscopy (ES‐MS), Fourier transform infrared (FTIR), and fluorescence spectroscopy to be hydrolysis of the ester linkage between the C‐terminus (kynurenine) and the side chain of the fourth residue (threonine). The reaction was first order with respect to time; however, the reaction order with respect to substrate concentration was <1 at substrate concentrations >1 mM. Insignificant buffer effect was observed. The reaction was subject to specific base catalysis. Activation parameters were Ea = 13.6 kcal/K·mol, ΔH‡ = 13.0 kcal/K·mol, and ΔS‡ = −19.2 eu. The positive primary salt effect was observed with negative deviation at high concentration of salt. The magnitude of the salt effect depended on salt identities in the order sodium < potassium < calcium chloride. © 2001 Wiley‐Liss, Inc. and the American Pharmaceutical Association J Pharm Sci 90:1066–1075, 2001